The beneficial pleiotropic effects of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) within the vasculature: A review of the evidence. (April 2016) - Forde, Hannah; Harper, Emma; Davenport, Colin; Rochfort, Keith D.; Wallace, Robert; Murphy, Ronan P.; Smith, Diarmuid; Cummins, Philip M.
Abstract: Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a type II transmembrane protein that belongs to the tumour necrosis factor (TNF) cytokine superfamily. TRAIL is expressed by numerous cell types including vascular cells, immune cells and adipocytes. Although originally thought to induce apoptosis in malignant or transformed cells only, it is now known that TRAIL can bind up to 5 distinct receptors to activate complex signalling pathways, and is capable of exerting pleiotropic effects in non-transformed cells. In this respect, a number of clinical and animal studies point to the potential vasoprotective influence of TRAIL, with TRAIL deficiency being linked to accelerated atherosclerosis and vascular calcification. Moreover, exogenous TRAIL administration has been shown to exhibit anti-atherosclerotic activity in-vivo . In-vitro studies on TRAIL in this context have yielded conflicting results however, with evidence of both pro-atherogenic and vasoprotective effects ascribed to TRAIL. Notwithstanding these various studies, mechanistic information on the precise nature of TRAIL-mediated injury/protection within the vasculature, as well as the identity of the downstream molecular/cellular targets of TRAIL, is still quite limited. In this review, we will summarize our current knowledge of TRAIL regulation, signalling mechanisms, and its apparent involvement in CVD pathogenesis as a prelude to examining the existing evidence for TRAIL-mediated vasoprotection. To this end, extensive in vitro, in vivo, and clinical studies will be reviewed and critical findings highlighted. Highlights: TRAIL regulation, signalling and interaction with both vessel wall and circulating cells is examined. The effects of TRAIL blockade, knockdown, overexpression and administration in animal models is summarized. We consider both basic and clinical evidence in support of atherogenic versus vasoprotective roles for TRAIL in vivo . The diagnostic and therapeutic potential of TRAIL is discussed.